2017
DOI: 10.3390/molecules22081224
|View full text |Cite
|
Sign up to set email alerts
|

Extracts Obtained from Pterocarpus angolensis DC and Ziziphus mucronata Exhibit Antiplasmodial Activity and Inhibit Heat Shock Protein 70 (Hsp70) Function

Abstract: Malaria parasites are increasingly becoming resistant to currently used antimalarial therapies, therefore there is an urgent need to expand the arsenal of alternative antimalarial drugs. In addition, it is also important to identify novel antimalarial drug targets. In the current study, extracts of two plants, Pterocarpus angolensis and Ziziphus mucronata were obtained and their antimalarial functions were investigated. Furthermore, we explored the capability of the extracts to inhibit Plasmodium falciparum he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 30 publications
(62 reference statements)
2
5
0
Order By: Relevance
“…Tables 2 and 3 resume the analysis of the phenolic compounds for both plants. It was verified that gallic acid is not abundantly present in the crude extracts and fractions of J. paniculata and P. angolensis, as it was also previously reported for P. angolensis extracts [19]. Similar results were observed for caffeic acid and taxifolin [19].…”
Section: Phytochemical Characterization and Phenolic Profilesupporting
confidence: 87%
See 3 more Smart Citations
“…Tables 2 and 3 resume the analysis of the phenolic compounds for both plants. It was verified that gallic acid is not abundantly present in the crude extracts and fractions of J. paniculata and P. angolensis, as it was also previously reported for P. angolensis extracts [19]. Similar results were observed for caffeic acid and taxifolin [19].…”
Section: Phytochemical Characterization and Phenolic Profilesupporting
confidence: 87%
“…It was verified that gallic acid is not abundantly present in the crude extracts and fractions of J. paniculata and P. angolensis, as it was also previously reported for P. angolensis extracts [19]. Similar results were observed for caffeic acid and taxifolin [19]. It is difficult to compare the results now obtained for J. paniculata, since, to the best of our knowledge, this is the first study reporting its phenolic profile.…”
Section: Phytochemical Characterization and Phenolic Profilesupporting
confidence: 79%
See 2 more Smart Citations
“…EGCG exhibited antiplasmodial activity with IC 50 of 2.9 µM, compared to CQ which registered IC 50 of 8.5 nM under similar growth conditions [118]. Interestingly, a plant extract enriched in epicatechin, which is structurally closely related to EGCG, also inhibited P. falciparum Hsp70 and exhibited antiplasmodial action [119]. This suggests that at least some parasite Hsp70s are essential for normal parasite growth, but these studies have not yet found support from reverse genetics, probably due to the hesitation by researchers to attempt to knock out a gene which is highly likely to be essential.…”
Section: Implications For Therapeutic Interventionmentioning
confidence: 99%